A detection method of gear micro-cracks based on tuned resonance. (December 2021) - Li, Rui; Cui, Xiaoling; Zhao, Yang; Feng, Xu; Dong, Jikun
Highlights: The vibration characteristics of gear defects under resonance condition is studied. A method of gear defect detection based on tuning resonance was proposed. A new gear defect feature extraction algorithm is proposed. The algorithm is helpful to identify the gear defect features under non-tuned state. Gear defect features are more obvious and easier to extract under resonance state. Abstract: Detection of micro-cracks before assembling has always been a challenge in gear defect detection. A mature detection method of micro-cracks is not available. Due to the complex detection environment and large production of gears, it's urgent to develop a rapid and accurate detection method of gear micro-cracks. It's the key to separate and extract weak vibration signals accurately under complex disturbances in gear defect detection. In this study, vibration characteristics of gear defects under resonance conditions were firstly explored and a detection method of gear micro-cracks was proposed based on tuned resonance. Based on the amplification effect of tuned resonance on the peak frequency spectrum of gear vibration, meshing frequency and sideband frequency characteristics of the gear defect signal spectrum were experimentally investigated. The amplitudes of gear meshing frequency and its harmonic meshing frequency in the signal frequency domain diagram were higher and the surrounding sideband frequency components were clearer.